A genetically-encoded reporter of synaptic activity in vivo - Dreosti, Elena (2009)
To image synaptic activity within neural circuits, we have tethered the genetically-encoded calcium indicator (GECI) GCaMP2 to synaptic vesicles by fusion to synaptophysin. The resulting reporter, SyGCaMP2, detects the electrical activity of neurons with two advantages over existing cytoplasmic GECIs: the locations of synapses are identified and the reporter displays a linear response over a wider range of spike frequencies. Simulations and experimental measurements indicate that linearity arises because SyGCaMP2 samples the brief calcium transient passing through the presynaptic compartment close to voltage-sensitive calcium channels rather than changes in bulk calcium concentration. In vivo imaging in zebrafish demonstrates that SyGCaMP2 can assess electrical activity in conventional synapses of spiking neurons in the optic tectum as well as graded voltage signals transmitted by ribbon synapses of retinal bipolar cells. Localizing a GECI to synaptic terminals provides a strategy for monitoring activity across large groups of neurons at the level of individual synapses.